Kemandirian Petani dalam Mengelola Usahatani Sayuran di Kota Denpasar - SUCITAYASA, I WAYAN; DARMAWAN, DWI PUTRA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p10, 2018)
Self-Reliance of Farmers in Managing Vegetable Farming in Denpasar City The development of urban agriculture has many challenges such as the difficulty of obtaining production inputs, the difficulty of obtaining credit, the limited of resources, the limited time, and the agricultural sector which is not a priority sector. Difficulties in farming in urban areas can be minimized with the self-sufficiency of each farmer. The purpose of the study was to investigate how the performance of vegetable farming management and how the level of self-sufficiency of vegetable farmers in Denpasar, as well as what factors influence the self-sufficiency of vegetable farmers in the city of Denpasar in terms of capital, production and marketing that are categorized in three classes of measurement i.e. less selfsufficiency, moderate self-sufficiency or full self-sufficiency analyzed by qualitative descriptive method. The results showed that vegetables farming conducted by farmers in the city of Denpasar was still classified as a traditional that rely on habits. The self-sufficiency seen from the aspects of capital, production and marketing can be categorized as medium category. Factors that affect the self-sufficiency in the capital aspect was age. The self-sufficiency in the aspects of production was influenced by the source of information, and the self-sufficiency in the marketing aspect was influenced by the partnership relationship. Based on the results of the research, it is recommended to increase the extension to increase knowledge of farmers related to vegetable agribusiness.